An Analysis Framework for Defining the Required IT&C Competencies for the Accounting Profession - Catalin Georgel Tudor; Mirela Gheorghe; Mirela Oancea; Robert Sova (Journal of Accounting and Management Information Systems (JAMIS), 2013)
In the current economic context, the issue of IT&C competencies indissoluble to the accounting profession gets special meanings: accounting skills and those associated with the quality of professional accountant must be completed with the specific use of advanced technologies to address this profession. This paper proposes an analysis of key competencies concerning the use of information and communication technology by the professional accountant, by defining a multidimensional analysis framework following, from different perspectives considered to be essentials, the opportunity to include IT&C competencies into training and professional development programs for accountants and auditors. This framework captures IT&C competencies located at the intersection of three axes (Roles, Levels of experience and Information technologies) that will guide the definition of thematic areas and specific competences. Finally, we identified correlations between the IT&C competencies and some important information technologies addressing the training programs for the accounting profession at different levels of expertise.
Keywords: M40; I21; 650; IT&C competencies; skills; knowledge of IT; IT technologies; accounting profession